AMBIVALENSI HUKUM PERKAWINAN ORANG TUA DENGAN ANAK ANGKAT BERDASARKAN HUKUM ADAT DAN HUKUM POSITIF INDONESIA - Julaeha, Siti (Istinbath : Jurnal Hukum, 2022)
The marriage of parents with adopted children is an act that is considered taboo by the majority of Indonesian people because, for the community, adopted children are on the same level as their biological children. This paper aims to discover the ambivalence of Indonesian customary law and positive law regarding marriage. The research method uses normative legal research with a comparative approach to law and legislation. The marriage of parents with adopted children creates legal conflicts in society. According to customary law, this conflict occurs because adopted children are considered their children, as Kluet, Bali, and Java indigenous peoples apply. According to the tradition of indigenous peoples, when someone is adopted as a child, he is considered a biological child. In addition, Law no. 35 of 2014 and PP No. 54 of 2007 implicitly in its articles indicate that this type of marriage is not allowed. Meanwhile, Law no. 1 of 1974 implies the permissibility of this type of marriage in the provisions of its articles. Based on this, it can be seen that there has been legal ambivalence regarding the implementation of the marriage of parents with adopted children in Indonesia. The author argues that it is crucial to synchronize customary and normative laws to eliminate legal ambivalence and create legal certainty for this type of marriage.